61.2k views
2 votes
Can anybody help me? Thank you for your answers​

Can anybody help me? Thank you for your answers​-example-1

1 Answer

1 vote

Answer:

x = 2y

Explanation:

we don't need to do complicated trigonometric conversions. just try to express x by a term of y (or vice versa) and look.

so, starting with x = 2y.

if that is the case, then what is our equation looking like ? is it true ?

sin(2y - y)/sin(y) + cos(y - 2y)/cos(y) = 2

sin(y)/sin(y) + cos(-y)/cos(y) = 2

1 + cos(-y)/cos(y) = 2

cos(-y)/cos(y) = 1

cos(-y) = cos(y)

and yes, this is indeed true for all y. cos decreases from 1 to -1 with the increase of the absolute value of the angle from 0 to 180 degrees (meaning we could go up or down the same angle from 0, and cos would be the same), and then increases again to +1 for the increase of the absolute value of the angle from 180 to 360 degrees. and then it all starts again. and again, and again, ...

so, since the original equation is true under the assumption x=2y, this must be the correct option.

User Iavr
by
5.5k points